Chemical-vapor-deposited 2D VSe2 nanosheet with threshold switching behaviors for Boolean logic calculations and leaky integrate-and-fire functions. Issue 15 (14th March 2023) - Zhong, Lun; Xie, Wanxuan; Yin, Jinxiang; Jie, Wenjing
Abstract : Reliable threshold switching behaviors can be observed in VSe2 nanosheets after an annealing method owing to the phase transition from the 1T to 2H. The VSe2 memristor can be employed to perform Boolean logic calculations and simulate LIF functions. Abstract : The leaky integrate-and-fire (LIF) model of artificial neurons has been widely studied owing to its potential applications in performing signal integration, firing function and the decay of local gradient potential in artificial neural networks. The threshold switching (TS) memristors have been considered to be one of the most promising candidates for simulating LIF activity owing to its self-resetting property. In this work, VSe2 nanosheets are synthesized by the chemical vapor deposition method and the phase transition from the 1T to 2H is achieved in the prepared nanosheets through an annealing method. The annealed VSe2 nanosheets demonstrate decent and reliable TS behaviors with good endurance, repeatability and good environmental stability. The VSe2 memristor not only demonstrates the possibility to realize the logic operations of "NOT", "AND" and "OR", but also provides a promising solution for the simulation. This work presents a feasible approach to TS behaviors, which broadens the applications of VSe2 materials and provides potential candidates for realization of Boolean logic calculations and LIF functions.